Sensory profile´¨s characterization of neaded cheese in the Carhi province - Paredes Pita, Carlos Arturo; Cadena Mafla, Vanessa Elizabeth; Bolaños Fuel, Cinthya Katherine (Tierra Infinita, 2022)
Fresh cheeses have a great influence on the lifestyle of the habitants from the northern zone, despite this, their production technology has been partially studied however there are not studies regarding the sensory characterization and texture profile of fresh cheeses in Ecuador. Consumer acceptance of a product will depend on many factors, mainly on its sensory properties. In the present investigation, the sensory profile of the kneaded cheese from the Carchi province was established. We worked with the association of northern dairy producers (ASPROLAC) from which seven producers were selected, the sensory profile of the kneaded cheeses was determined in appearance, smell / taste and sensorial texture characteristics, to carry out this study a panel of twenty one members were trained, they were specialized in sensory evaluation of cheese following the technique of quantitative descriptive analysis (QDA). The sensory profile of the cheese was obtained by averaging the values assigned to each descriptor, with an intensity of odor 2.73, intensity of aroma 2.66 for salty curd and cooked milk, sweet taste 1.06, acid 1.24, salty 4.5, bitter 1.13, with low persistence. In relation to the texture, it indicates that the kneaded cheese is a cheese that presents a high impression of humidity, with a medium intensity in terms of elasticity, firmness, adhesion, solubility, creaminess, friability, granularity, and guminess, also these characteristics make it the easily chewy kneaded cheese, generating the food bolus with a reduced number of chews, besides these features added to the other textural characteristics, generate pleasant sensations in the mouth.